2020
DOI: 10.7566/jpsj.89.043703
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Response of Majorana Kramers Pairs Protected by \(\mathbb{Z}_{2}\) Invariants

Abstract: On the surface of time-reversal-invariant topological superconductors, Kramers pairs of Majorana fermions with chiral and crystalline symmetries exhibit completely uniaxial or octupole anisotropic magnetic response. This paper reports possible types of magnetic responses of Majorana Kramers pairs with one-dimensional Z 2 invariants defined by crystalline symmetry. In particular, the general theory predicts a new type of magnetic response where two Majorana Kramers pairs associated with the Z 2 invariant show b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Thus, the magnetic response of MKPs gives a way to identify unconventional Cooper pairs in TSCs. More recently, we extended the above discussion to the case of MKPs ensured by crystalline symmetry-protected Z 2 invariant, and revealed that TSCs with nonsymmorphic symmetry naturally host two MKPs, leading to an electric quadrupole response 65,66 .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, the magnetic response of MKPs gives a way to identify unconventional Cooper pairs in TSCs. More recently, we extended the above discussion to the case of MKPs ensured by crystalline symmetry-protected Z 2 invariant, and revealed that TSCs with nonsymmorphic symmetry naturally host two MKPs, leading to an electric quadrupole response 65,66 .…”
Section: Introductionmentioning
confidence: 76%
“…In order that Ĥm is invariant under G k 0 , g + (B) (g − (B)) and ÔMF+ ( ÔMF− ) should be the same irrep under the transformation in Eqs. ( 64) and (65).…”
Section: E Electric and Magnetic Couplings Of Mkpsmentioning
confidence: 99%
“…An interesting extension of our study is for topological superconductors, on Majorana fermions The surface Majorana fermions timereversal-invariant topological have only Ising of freedom for called Majorana Ising spins. Furthermore, an octupole [29] and an (electric) quadrupole [30] of Majorana fermions can be coupled to a magnetic that the magnetic-texture-induced Hall effect is used to detect Majorana fermions and their magnetic degrees of freedom; this will be discussed in a future work.…”
mentioning
confidence: 99%
“…It has previously been revealed that double MKPs protected by crystalline symmetry can respond to an electric perturba-tion. 44) The electric responses of MKPs have also been classified for each superconducting pair potential when the symmetry of the surface is or 4 wallpaper group (WG). 43) Thus, although several properties of the electrical response of double MKPs have been clarified discursively, this study comprehensively clarifies new aspects of the electrical response from a different perspective.…”
mentioning
confidence: 99%
“…These phenomena have been systematically classified. 27-30, 32, 45) According to these classifications, double MKPs can only exist in magnetic chiral-and/or glide-planesymmetric systems, 30,42,44,46) as described below.…”
mentioning
confidence: 99%